FEATURES OF SEMANTIZATION OF VALUES OF WORDS IN EXPLANATORY DICTIONARIES OF ADYGHIAN LANGUAGES - O. A. SHOKAROVA (Кавказология)
The article is devoted to the study of the specificity of semantization (interpretation and description) of lexemes in the explanatory dictionaries of the Adyghian languages. The author aims to identify the characteristic features of filiation (selection) of meanings and interpretation of words, the basic principles of their description. Special attention is paid to aspects such as completeness and accuracy in the interpretation of tokens. During the analysis of vocabulary articles presented in the Adyghian dictionaries, two principles of the semantization of words and concepts were identified. The results of the study can be applied in the field of linguistic research.